Understanding the purposeful journey of an Korean archery coach group’s self-directed professional development: a qualitative exploration of coaching expertise enhancement - Heonjae Lee; Ooksang Cho (Cogent Social Sciences)
The purpose of this study was to delve into the motivational processes that facilitate the development of professional expertise among Korean archery coaches as educators, through their commitment to voluntary professional development. Additionally, the study aimed to investigate the underlying reasons for their sustained success in producing world-class athletes. Three male archery coaches, each with over 30 years of experience coaching athletes, including experience coaching the South Korean national team, participated in this study. They played a pivotal role in shaping the national archery team and remained actively engaged in the archery community as coaches and administrators. Data were collected through in-depth interviews with a focus on identifying the educational strategies that have consistently led to success among archery coaches. Utilizing analytic induction, this study sought to determine themes related to participants’ coaching knowledge and philosophies. The findings reveal that despite early retirement due to external environmental factors, these participants displayed a strong dedication to excelling in their roles as coaches rather than athletes. They exhibited a clear vision of the future and maintained a proactive readiness for various scenarios. This study posits that these individuals not only fulfill the role of coaches in the realm of archery, but also function as educators.